International Journal of Earth Sciences - International Journal of Earth Sciences (Springer Nature, 2026)
International Journal of Earth Sciences is a comprehensive resource for research and review papers on earth's history and processes.
FI 0.53
Q3
Keywords: Earth; Space & Environmental Sciences; Geology & Geophysics; Geología; Geofísica; Acuerdos transformativos; Transformative agreements; Evolución de la vida; Tectónica; Vulcanología; Sedimentología